SSA fractionation of thermoplastic polyurethanes. Issue 1 (25th August 2020) - Fernández‐d'Arlas, Borja; Maiz, Jon; Pérez‐Camargo, Ricardo A.; Baumann, Roelf‐Peter; Pöselt, Elmar; Dabbous, Raphael; Stribeck, Almut; Müller, Alejandro J.
Abstract: The successive self‐nucleation and annealing (SSA) thermal fractionation technique has been applied for the first time to thermoplastic polyurethanes (TPUs). The changes in structure and morphology before and after SSA fractionation were monitored by Differential Scanning Calorimetry (DSC), in situ real‐time Small and Wide‐angle X‐ray scattering synchrotron experiments (SAXS/WAXS) and Atomic Force Microscopy (AFM). SSA applies a series of successive cooling and heating runs to a self‐nucleated sample that promotes the creation of a series of thermal fractions in the TPUs with a specific lamellar thicknesses and melting point distribution thanks to the multi‐block structure of TPUs. The SSA fractionated samples experienced a general increase in lamellar thickness that has been revealed by both AFM and SAXS and a distribution of lamellar thickness estimated by DSC and AFM. The average lamellar thickness of SSA fractionated samples has been estimated by SAXS, AFM, and DSC. The values obtained are in quantitative agreement (within the errors involved in the techniques) when considering that phase segregation in the TPU samples has been promoted by crystallization. The refined crystalline structure obtained after SSA produced a number of clear WAXS reflections, as compared to the unfractionated materials, facilitating the determination of the TPUs crystallinity degree by WAXS. Abstract : Successive self‐nucleation and annealing can successfully fractionate TPUs (as a result of their multi‐block structure) producing well‐defined thermal fractions with distinct melting points. SSA provoked a significant increase in average lamellar sizes (determined by AFM, SAXS, and DSC) and a refinement of the crystalline structure as revealed by WAXS. The SSA technique can be employed as a valuable characterization tool for TPUs.